ANALISIS PERBEDAAN KEMAMPUAN BERFIKIR KREATIF SISWA MELALUI MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN EKONOMI KELAS X IIS SMA NEGERI 15 PEKANBARU - Ayu Andriani; Caska Caska; Henny Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research aims to know the difference in the ability of students ' creative thinking through the application of the learning Teams model Games Tournament (TGT) on economic subjects X-grade IIS in SMA Negeri 15 Pekanbaru. The population of the research was to grade X as much as 72 students and all was made of a sample of research. The data collected using the technique of the now. Analyzed by Independent t-Test Analysis Test results. find the existence of significant differences of creative thinking ability of students through the application of pembeljaran model Times Games Tournament (TGT) control class and the class experiments with value significant 0.000 < 0.05. Thus it can be concluded that the application of the learning Teams model Games Tournament (TGT) is better than using a model learning lectures, and an increase in the ability of the creative thinking of the students key words:: thinking ability Creative Learning Times Games Tournament (TGT)Keywords: The Ability To Think Creatively, A Model Of Learning Times Games Tournament (TGT)